Modos de presentación y modos de determinación - Maite Ezcurdia (Crítica)
In this paper I argue that, in order to make (T1) and (T2) compatible within a Fregean approach, we must reject the view that all modes of presentation are senses. (T1) There is a diversity of ways in which Venus may be presented to each subject, and which are associated with the name ‘Venus’. (T2) There is only one Fregean thought expressed by the sentence ‘Venus is a planet’. Modes of presentation are those things which are essentially psychological and have causal powers on minds. The mind of a subject is sensitive to differences in modes of presentation, so that if an object is presented to a subject under different modes of presentation and she has no reason to believe that they are modes of presentation of one and the same object, then she may take opposing attitudes involving those different modes of presentation. In contrast, senses are those things which are essentially semantic. For this reason, I propose that they be understood as certain ways of determining the reference of terms, and either are given by the semantic rules for those terms or are identical to those semantic rules. I agree with McDowell that an interpretive truth-theory for a language L gives us a theory of sense for L, and that something like (V) ‘Venus’ refers to Venus will give us the axiom which assigns the semantic value for ‘Venus’ within such a theory, and which is necessary in order to derive the interpretive truth-conditions of a sentence like ‘Venus is a planet’. An axiom like ‘Venus’ refers to Hesperus will not do within a theory of sense. Nonetheless, it will do within a theory of reference, a truth-theory which delivers not interpretive truth-conditions, but purely referential truth conditions. The purely referential truth-conditions for an indicative atomic sentence are, I claim, those which are specified by specifying those features in the world (objects, properties, etc.) to which the meaningful parts of the sentence refer, representing them as related in a certain way. For the specification of such truth-conditions, the difference in cognitive value between two sentences will not matter, whereas it will matter for the specification of interpretive truth-conditions. Now, senses are introduced to allow for an explanation of the difference in cognitive value between sentences with the same purely referential truth-conditions. An indication of when two sentences differ in cognitive value is when it is possible for a subject who is rational and understands the language in question to take opposing attitudes to those sentences (or their contents —whatever those contents are); and if there is in fact such a subject who takes opposing attitudes to those sentences, then those sentences differ in their cognitive value. Given this connection between cognitive value and a subject’s attitudes, and given the purpose for which senses are introduced, we must suppose that a subject’s mind must be sensitive to differences in senses, and so, that senses must be psychologically relevant. My proposal, which aims to establish some kind of identity between some modes of presentation under certain conditions and those ways of determination which are senses, is as follows: A psychological mode of presentation M is a way of determination which is a sense relative to a particular expression e in a public language L which aids in expressing propositional attitude P if and only if i the subject who has M and who is sufficiently competent in L knows (or realizes) that M goes with e in L; ii no other proposition e′ in L is more adequate for reporting the subject’s propositional attitude P; iii M is crucial in the subject’s rational failure to make certain identifications; and iv M is an appropriate function to an appropriate reference. Only the mode of presentation associated with ‘Venus’ that satisfies conditions i-iv relative to ‘Venus’ which aids in expressing a propositional attitude like the belief that Venus is a planet, will be the sense of ‘Venus’. I argue that only the mode of presentation of Venus as Venus will do, and that such mode of presentation is implicit in the way of determination shown by (V). Other modes of presentation of Venus as being big or appearing in the sky in the evenings or being the second planet in proximity to the sun will not satisfy conditions i–iv. Thus, although a subject may have all these modes of presentation of Venus and associate them with ‘Venus’ (i.e. (T1)), only the mode of presentation of Venus as Venus will do as the sense of ‘Venus’. Hence, only one thought will be expressed by a sentence like ‘Venus is a planet’ (i.e. (T2)).